The Effect of Work Discipline and Work Allowances on Employee Performance through Work Attachment to the Regional Revenue Agency of Madiun Regency - Puspita, Karina Endhy; Askafi, Eka; Mulyaningtiyas, Ratna Dewi (Jurnal Ilmiah Sumber Daya Manusia, 2025)
Employee performance plays a crucial role as a benchmark for public service delivery by local governments in serving the community. Employee performance is often linked to the implementation of work discipline and is influenced by the work allowances received by civil servants. This study aims to analyze the influence of work discipline and work allowances on employee performance through work engagement at the Madiun Regency Regional Revenue Agency. This quantitative study involved 42 respondents, consisting of all civil servants at the Madiun Regency Regional Revenue Agency, selected using a saturated sampling technique. Data were collected through an online questionnaire and analyzed using SmartPLS4 software. The results of the study indicate that work discipline has a significant effect on work engagement, work benefits have a significant effect on work engagement, work discipline has a significant effect on employee performance, work benefits have a significant effect on employee performance, work engagement has a significant effect on employee performance, work discipline has a significant effect on employee performance through work engagement,  and work benefits have a significant effect on employee performance through work engagement. The results of this study indicate that work discipline and work benefits through work engagement are key factors in improving employee performance. The implication of this study is that local governments should prioritize the implementation of work discipline and the provision of work benefits that are appropriate to the workload and work performance through work engagement can improve employee performance which has an impact on improving public services carried out by the government.